Retrospective audit on outcomes of post caesarean section sepsis after additional azithromycin to the standard antibiotic at Tygerberg hospital, Cape Town - Matabata, Thembani; Mbungu, Nomaphelo; Singini, Isaac (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.